The determinants of house price in Malaysia / Amira Nabila Amir Mustafa - Amir Mustafa, Amira Nabila (Faculty of Business and Management, 2018)
The main purpose of this study is to determine the determinants of housing price in malaysia on yearly basis from year 1980 to 2016. There are five determinant relate with housing price which is interest rate (INT), inflation rate (INF), gross domestic product (GDP), population (POP) and unemployment rate (UNE). These result further understanding about the relationship between housing price and other variable. The result indicates that there are significantly related to house price using time series data. As result is interest rate, GDP, and unemployment rate show significant positive relationship with house price. Otherwise, population show significant negative towards house price. The paper is useful for investors, speculators, policies makers and buyers to know which factors to account for in housing investment decision. This paper can also serve as a guide for the government in stabilizing the residential housing price in Malaysia.